Lun zi shang de Mai Xiaomai - Yin, Jianling 1971- (Cai wu ya zhong wen yuan chuang xi lie, 2013)
Where do I come from? How should I face my biological mother, who once abandoned me? These are the tough questions the heroines of the story suddenly have to answer. The cruel reality makes Mai Xiaomai and Mai Xiaoye suspicious, scared, bitter and annoyed, but in the end, they chose to be tolerant and accepting. (e-BIBF)